Liderança do treinador e satisfação de atletas escolares - Rodrigues, Vinícius de Matos (2014)
Although leadership is a widely studied phenomenon by researchers in the social sciences, little is known about its effects in the sport context. Leadership has been neglected, especially in school sports. On the other hand, school sports have absorbed great investments to develop new athletes and promote the health of sport practitioners. In this context, the coach (leader) plays a key role, because his behavior influences, positively or negatively, the athletes' performance and psychological well-being. This study is based on the Multidimensional Model of Leadership, proposed by Chelladurai (1978, 2007), and had as its main objective to analyze the relationship between coaches' leadership and school athletes' satisfaction. The specific objectives were: (1) to make a descriptive and comparative study of coaches' leadership behavior and athletes' satisfaction; (2) to verify the correlation between the leadership perceived by the athletes and coaches self-perceived leadership; (3) to test the hypothesis of congruence of leadership with satisfaction and (4) to prepare an explanatory model of the athletes' satisfaction from the coach's leadership behavior. The sample consisted of 466 athletes with an average age of 16.16 (SD=0.79) and 57 coaches with an average age of 37.91 (SD = 9.52), participants of the 2012 National School Games, held by the organization of the Brazilian Olympic Committee. The athletes completed a sociodemographic questionnaire, the Leadership Scale in Sports (preference and perception versions) and the Athlete's Satisfaction Questionnaire (leadership version). The coaches, instead, completed the sociodemographic questionnaire the Leadership Scale in Sports (self-perception version). The analysis of internal consistency and factor analysis confirmed the psychometric validity of instruments. The intra- and inter-group comparisons (according to gender and modality type) showed differences in a few leadership and satisfaction dimensions. However, there was no difference between the responses of athletes and coaches, suggesting that there is an agreement on the behavior displayed by the coach. The results of the regression analysis partially support the hypothesis that the athletes' satisfaction is dependent on the congruence between athletes' preferred and perceived coaches. Lastly, the model developed shows three dimensions of the coach's leadership behavior as explanatory variables of the athletes' satisfaction.